2020
DOI: 10.1093/oep/gpaa017
|View full text |Cite
|
Sign up to set email alerts
|

House Price Shocks, Credit Constraints and Household Indebtedness

Abstract: We analyse the effect of housing wealth on household indebtedness in a life-cycle framework. Exploiting longitudinal household data and temporal and geographic variation in house prices, our empirical results indicate that households respond to increases in housing wealth by significantly increasing their debt. The effect is strongest for households that are moderately leveraged, highlighting the importance of collateral constraints. Furthermore, we uncover a weaker wealth effect from house price growth for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our results showed that the employed and self-employed household members showed decrease in household wealth. Households that suffered from negative income shocks or unemployment showed a weaker effect from house price growth (Atalay et al, 2020). In addition to employment status, the field of employment of the household's head and education are also important determinants of financial vulnerability (Ali, Khan and Ahmad, 2020).…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the employed and self-employed household members showed decrease in household wealth. Households that suffered from negative income shocks or unemployment showed a weaker effect from house price growth (Atalay et al, 2020). In addition to employment status, the field of employment of the household's head and education are also important determinants of financial vulnerability (Ali, Khan and Ahmad, 2020).…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…Moreover, income is intricately linked to household members' employment status, which affects the level of indebtedness. Temporary employment contracts and unemployment increase financial vulnerability, but a stable job increases the likelihood of savings and lowers the financial vulnerability of households (Atalay et al, 2020;Ali, Khan and Ahmad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature also suggests important factors that delay ownership may be associated with long-run changes in economic and social outcomes. Research show that house prices and tenure status have significant impacts on labour supply, consumption, indebtedness, and the health and fertility decisions of Australians (Atalay and Edwards 2022; Atalay, Barrett et al 2020;Atalay, Edwards et al 2017;Atalay, Li et al 2021;Atalay, Whelan et al 2017;Eccleston, Verdouw et al 2018). Hence, analysing how housing market conditions are associated with differences in home ownership is important for understanding broad economic and demographic trends in Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, people might move to a low inequality neighbourhood with the aim to reduce their debts. I follow Atalay et al (2020)…”
Section: Robustness Checksmentioning
confidence: 99%